Food neophobia: psychological dimensions of consumer perception and emotional sentiment in social media discourse - Shan, Yu; Wang, Hong; Wang, Wenqi (Frontiers in Nutrition, 2025)
Addressing global food security necessitates exploring future foods, yet their societal acceptance hinges critically on public perception an2d psychological barriers such as neophobia. This study delves into the psychological dimensions underlying consumer perception of future foods, investigating the intricate relationship between food neophobia and these perceptions, and mapping the prevailing emotional landscape surrounding novel food adoption. Employing a Social Media Analytics (SMA) framework to capture ecologically valid public discourse, we utilized social media text analysis, integrating topic modeling and sentiment analysis, to dissect online expressions concerning future foods. Our analysis reveals that public evaluations are predominantly positive (53.20%), while a substantial segment expresses negative sentiments (30.48%) and ambivalence (16.32%). Psychologically, we identified four salient perceptual dimensions – taste, appearance, culture, and technology – which differentially mediate food neophobia and elicit distinct emotional valences. Notably, appearance and cultural perceptions are associated with heightened neophobia and negative emotional responses, suggesting underlying psychological mechanisms of sensory and socio-cultural rejection. These findings offer critical psychological insights for future food producers and policymakers, highlighting the psychological determinants of public attitudes toward future foods and informing psychologically-informed strategies to enhance consumer acceptance and promote dietary innovation.